Uno más uno, tres (2017)
Uno más uno, tres is a project that consists on a series of paintings. These paintings consists on two elements: monochrome and skies. Each of these elements occupy the same pictorical space. They have different characteristics which create contrast and duality in the techinique as well as in the concepts. Monochrome in this work is glossy and almost reflective. It represents how the industrial world is very synthetic and artificial. On the other hand, the skies represent the ephemeral and organic. When the monochrome and the fragments of the sky are together they create a third element, la línea. This new element occurs between the monochrome and the skies and creates a duality between them. La línea, only exists if the other two do.